2020
DOI: 10.1016/j.virusres.2020.197863
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel monoclonal antibodies against MERS-coronavirus spike protein

Abstract: Middle East Respiratory Syndrome coronavirus (MERS-CoV) causes severe pulmonary infection, with ∼35 % mortality. Spike glycoprotein (S) of MERS-CoV is a key target for vaccines and therapeutics because S mediates viral entry and membrane-fusion to host cells. Here, four different S subunit proteins, receptor-binding domain (RBD; 358-606 aa), S1 (1-751 aa), S2 (752-1296 aa), and SΔTM (1-1296 aa), were generated using the baculoviral system and immunized in mice to develop neutralizing antibodies. We developed 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 30 publications
0
41
0
2
Order By: Relevance
“…These mAbs bind to six specific epitope groups interacting with the receptor binding, membrane fusion, and sialic acid-binding sites, which represent the three important entry functions of MERS-CoV S protein. 21,38 Moreover, passive immunization with poorly and potently neutralizing antibodies induces substantial protection in mice subjected to lethal MERS-CoV challenge. Thus, use of these antibodies may represent a novel approach to increase humoral protection against emerging CoVs by targeting various S protein epitopes and functions.…”
Section: Passive Immunizationmentioning
confidence: 99%
“…These mAbs bind to six specific epitope groups interacting with the receptor binding, membrane fusion, and sialic acid-binding sites, which represent the three important entry functions of MERS-CoV S protein. 21,38 Moreover, passive immunization with poorly and potently neutralizing antibodies induces substantial protection in mice subjected to lethal MERS-CoV challenge. Thus, use of these antibodies may represent a novel approach to increase humoral protection against emerging CoVs by targeting various S protein epitopes and functions.…”
Section: Passive Immunizationmentioning
confidence: 99%
“…Recently, Wang and co-workers reported that Remdesivir, a nucleotide analogue prodrug initially developed for the treatment of Ebola and Marburg virus infection, and the anti-malarial drug chloroquine are effective to inhibit 2019-nCoV replication in vitro . Finally, the development and use of neutralizing monoclonal antibodies, as proposed in the case of SARS and MERS, could be envisioned for 2019-nCoV control as well (Kim et al 2019;Goo et al 2020). Many monoclonal antibodies neutralizing SARS-CoV and MERS-CoV infections have been identified, and some of them displayed a potent inhibitory effect in in vitro and in vivo experiments.…”
Section: The New 2019 Coronavirusmentioning
confidence: 99%
“…Genomic RNA is encapsulated and polyadenylated, and it encodes various structural and non-structural polypeptide genes (Cui et al 2019;Subissi et al 2014). These polyproteins are split by proteases that exhibit chymotrypsin-like activity (Subissi et al 2014;Goo et al 2020). The resulting complex drives (−) RNA production through both replication and transcription (Jordan et al 2018).…”
Section: Pathogenesismentioning
confidence: 99%
“…MERS-CoV can affect human dendritic cells, macrophages and T lymphocytes. This virus can make the antiviral T cell response irregular because of the stimulation of T cell apoptosis, thus causing a collapse of the immune system (Farooq et al 2020;Park et al 2019;Goo et al 2020;Cockrell et al 2016).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation